PENGARUH KUALITAS PELAYANAN DAN LOKASI USAHA TERHADAP KEPUASAN KONSUMEN PADA SMART GANESHA PEKANBARU - Windari, Indah; Karneli, Okta (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This research was conducted at Smart Ganesha Pekanbaru, located on Soebrantas street in Pekanbaru. The problem in this study is not achieving student targets during the last 4 years, this is suspected to be a problem with customer satisfaction. The purpose of this study is to determine the effect of service quality and business location on customer satisfaction on Smart Ganesha Pekanbaru. In this study the method used was descriptive quantitative with SPSS program. The sample of this study was 86 people from a population of 86 people who were obtained from census techniques. Data obtained from the results of the questionnaire were then processed to then be tested through the SPSS 16. The multiple linear regression analysis of this study was Y = 6.883 + 0.205XÄ± + 0.568X2. Research that has been done shows the results that respondents' responses to service quality and business location in the agreed category while in consumer satisfaction are in the category of disagree. While the t test that has been done shows that the variable quality of service and business location partially have a significant effect on consumer satisfaction. The results of the F test show that simultaneously service quality and business location have a significant effect on customer satisfaction. While the calculation of the coefficient of determination (R2) obtained the value of Adjusted R Square of 0.261. This shows that service quality and business location have an effect of 26.1% on consumer satisfaction on Smart Ganesha Pekanbaru, while the remaining 73.9% is influenced by other variables not included in this study.Â Keywords: Service Quality, Business Location, Constumer SatisfactionÂ